2013
DOI: 10.1038/cmi.2013.55
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4-mediated signaling regulates IL-7-driven proliferation and differentiation of B-cell precursors

Abstract: Lipopolysaccharide (LPS) is known to be a potent activator of mature B cells by signaling through Toll-like receptor 4 (TLR4). Its impact on early B-cell development, however, is not well defined. When comparing to C3H/HeN mice, TLR4-mutant C3H/HeJ mice showed an increase in the number of pro-B and pre-B cells in the bone marrow. When cultured in the presence of IL-7, the proliferation of pro-B and large pre-B cells was significantly inhibited by LPS, possibly due to reduced IL-7 receptor-a (IL-7Ra) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…While several inflammatory molecules including LPS are known to be activators of B cells at the maturation stage following export to the periphery, recent studies showed that the TLR4 signaling pathway inhibits proliferation of pro-B and pre-B cells, and promotes the differentiation to IgM + immature B cells in BM. 28 , 29 Consistent with previous studies, the suppression of B-cell differentiation in BM was observed 3 days following sub-lethal dosing of LPS treatment (1.0 mg/kg) ( Figure 6C ). When Tg mice were treated, the actual B-cell number in peripheral blood decreased and a significant reduction of B progenitors in BM was observed ( Figure 6C and D).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…While several inflammatory molecules including LPS are known to be activators of B cells at the maturation stage following export to the periphery, recent studies showed that the TLR4 signaling pathway inhibits proliferation of pro-B and pre-B cells, and promotes the differentiation to IgM + immature B cells in BM. 28 , 29 Consistent with previous studies, the suppression of B-cell differentiation in BM was observed 3 days following sub-lethal dosing of LPS treatment (1.0 mg/kg) ( Figure 6C ). When Tg mice were treated, the actual B-cell number in peripheral blood decreased and a significant reduction of B progenitors in BM was observed ( Figure 6C and D).…”
Section: Resultssupporting
confidence: 91%
“… 7 , 40 As far as the impact on B progenitors in BM is concerned, two research groups previously showed that signaling through TLR4 inhibits pro-B and pre-B proliferation, and enhances differentiation to IgM + immature B cells, using different methods. 28 , 29 In our genetically modified mice, STAP-2 displayed synergistic effects on pre-B-cell proliferation with the TLR4 pathway. However, STAP-2 effects did not involve differentiation to IgM + immature B cells.…”
Section: Discussionmentioning
confidence: 83%
“…LPS is a major component of the outer membrane of Gram-negative bacteria and has been used in mammals, amphioxus, fish and lamprey for immunological studies 32 33 34 35 . Consistently with these findings, we observed that the expression levels of VLRB and BLNK were upregulated approximately 2.5-fold in lymphocyte-like cells and supraneural myeloid bodies after stimulation with LPS ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may regulate the differentiation of B cell precursors by facilitating the generation of sIgM + immature B cells [44]. Recently, Li et al [45] confirmed the critical role of TLR4 in the proliferation and differentiation of B cell precursors in TLR4-mutant C3H/HeJ mice and TLR4-intact C3H/HeN mice. LPS-immunized C3H/HeJ mice showed an increase in the number of pro-B and pre-B cells in the bone marrow compared to LPS-immunized C3H/HeN mice.…”
Section: The Effects Of Tlr4 In Promoting the Proliferation Activmentioning
confidence: 99%